The Effect of Special Exercises Using Proposed Aids On Learning Long Jump Take off and Flight In National Center for Gifted in Athletics Aged (13-14 years) - Mustafa, Hussein; Juad, Zaidoon (Journal of Physical Education, 2019)
The research aim at designing special exercises using a designed apparatus in learning take off and flight in long jump for athletes aged (13 – 14) years old from specialized schools as well as identifying the effect of these exercises using a designed apparatus in learning take off and flight in long jump for athletes aged (13 – 14) years old. The researchers used the experimental method on (12) beginner athletes aged (13 – 14) years old selected from the specialized center for athletics; (2) were selected as pilot study subjects and (10) for applying the training program. The data was collected and treated using proper statistical operations to come up with the conclusions.